Effect of Governance on Tourist Arrival in Nepal - Sapkota, Naniram (Khwopa Journal, 2023)
It is believed that governance has a direct impact on all sectors of the state. This paper aims to examine the effect of governance on the tourism sector by adopting the Worldwide Governance Indicators (WGIs) produced by Kaufmann et al. (1999). For analyzing tourism sector performance, the annual number of tourists arriving in Nepal and their average length of stay have been taken separately from 2005 to 2019 as dependent variables. The six indicators of WGIs are taken as independent variables which include political stability and absence of violence, government effectiveness, voice and accountability, regulatory quality, rule of law, and control of corruption. The data were collected from secondary sources and analyzed by descriptive statistics using multiple-line graphs and regression models. The result shows that most of the WGIs insignificantly explained both the number of tourists and their length of stay. The finding differs for political stability and the absence of violence which significantly explains the relationship with the average length of stay per tourists. In a nutshell, the study concludes that governance-related indicators have not found a significant impact on tourist arrival in Nepal. Further, the findings of this study suggest reforming the existing level of all worldwide governance indicators for better performance of the tourism sector.